DEVELOPMENT OF A WEBSITE AS A MARKETING COMMUNICATION PLATFORM FOR EVENT SERVICES AT BOESA MANAGEMENT - Sarah Rouli Tambunan; Desmon Gunadi (Journal Analytica Islamica, 2026)
The rapid development of information and communication technology has encouraged companies to utilize websites as strategic marketing communication media. However, Boesa Management, a company operating in the event organizing industry, did not yet have an official website capable of integrating company information, services, portfolios, and customer interactions into a single platform. This study aimed to develop a website as a marketing communication platform for Boesa Management. The research employed a Research and Development (R&D) method. Data were collected through interviews, discussions with the company owner and marketing team, observations, and the collection of supporting documents. The development process included needs analysis, content collection, information architecture design, prototype development, website implementation, and evaluation. The results of the study indicate that the developed website successfully integrates company profiles, service information, portfolios, client testimonials, galleries, and event registration features into a structured and accessible platform. The website facilitates two-way communication between the company and its audience, strengthens brand identity, enhances corporate credibility, and improves the efficiency of event registration processes. The findings also reveal that successful website development depends not only on technical design and technological aspects but also on the organization’s ability to manage and update information effectively. Therefore, the website functions not only as a technological product but also as a strategic marketing communication instrument that supports business development and enhances competitiveness in the event organizer industry.